Quantification of urinary total luteinizing hormone immunoreactivity may improve the prediction of ovulation time - Demir, And; Hero, Matti; Holopainen, Elina; Juul, Anders (Frontiers in Endocrinology, 2022)
Objectives: Most of the currently available ovulation prediction kits provide a relatively rough estimation of ovulation time with a short fertility window. This is due to their focus on the maximum probability of conception occurring one day before ovulation, with no follow-up after LH surge until ovulation nor during the subsequent days thereafter. Earlier studies have shown that urine of reproductive age women contains at least 3 different molecular forms of luteinizing hormone (LH); 1) intact LH, 2) LH beta-subunit (LHβ) and a 3) small molecular weight fragment of LHβ, LHβ core fragment (LHβcf). The proportion of these LH forms in urine varies remarkably during the menstrual cycle, particularly in relation to the mid-cycle LH surge. In this exploratory study, we studied the potential implications of determining the periovulatory course of total LH immunoreactivity in urine (U-LH-ir) and intact LH immunoreactivity in serum (S-LH-ir) in the evaluation of the fertility window from a broader aspect with emphasis on the post-surge segment. Methods: We determined total U-LH-ir in addition to intact S-LH-ir, follicle-stimulating hormone (FSH), progesterone, and estradiol in 32 consecutive samples collected daily from 10 women at reproductive age. Inference to the non-intact U-LH-ir levels was made by calculating the proportion of total U-LH-ir to intact S-LH-ir. Results: Total U-LH-ir increased along with LH surge and remained at statistically significantly higher levels than those in serum for 5 consecutive days after the surge in S-LH-ir. S-LH-ir returned to follicular phase levels immediately on the following day after the LH surge, whereas the same took 7 days for total U-LH-ir. Conclusions: The current exploratory study provides preliminary evidence of the fact that U-LH-ir derived from degradation products of LH remains detectable at peak levels from the LH surge until ovulation and further during the early postovulatory period of fecundability. Thus, non-intact (or total) U-LH-ir appears to be a promising marker in the evaluation of the post-surge segment of the fertility window. Future studies are needed to unravel if this method can improve the prediction of ovulation time and higher rates of fecundability in both natural and assisted conception.